A nalysis of consumer choice based attributes of rice in the market: A case of Morogoro urban market - Lauwo, Godfrey Ephraim (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Science in Economics (MSc. ECONOMICS) of Mzumbe University